Areca catechu L. Nut Extracts’ Phytochemical Extraction and Comparative Investigation of their Antioxidant Properties - A. Ajesh Kumar; S. S. Syed Abuthahir; Hassan Y. Aboul-Enein (Novel Aspects on Pharmaceutical Research Vol. 2, 2023)
This chapter aims to compare the antioxidant properties of different solvent extracts of Areca catechu L. The FRAP assay demonstrated that all Areca catechu L. nut extracts have antioxidant capabilities because their IC50 values are lower than that of ascorbic acid. The remaining antioxidant assays, such as DPPH radical scavenging, H2O2 scavenging, and Fe2+ chelating, revealed higher antioxidant activities in ethyl acetate extract and nonpolar solvent extracts such as n-hexane and chloroform. Half maximal inhibitory concentration (IC50) of ethyl acetate and n- hexane extracts of Areca catechu L. nut is less than that of the IC50 of ascorbic acid in DPPH radical scavenging assay and hydrogen peroxide scavenging activity respectively. Antioxidant properties of Areca catechu L. nut vary depending upon the different solvent extract. More research on the therapeutic effects of Areca catechu L. nut will be conducted as a result of the isolation of components from various solvent extracts.